Embryonic Exposure to Valproic Acid Affects Social Predispositions for Dynamic Cues of Animate Motion in Newly-Hatched Chicks - Lorenzi, Elena; Pross, Alessandra; Rosa-Salva, Orsola; Versace, Elisabetta; Sgadò, Paola; Vallortigara, Giorgio (Frontiers in Physiology, 2019)
Early predispositions to preferentially orient towards cues associated with social partners have been documented in several vertebrate species including human neonates and domestic chicks. Human newborns at high familiar risk of Autism Spectrum Disorder (ASD) show differences in their attention toward these predisposed stimuli, suggesting potential impairments in these social-orienting mechanisms in ASD. Using embryonic exposure to valproic acid (VPA) we modelled ASD behavioural deficits in domestic chicks. To investigate social predispositions towards animate motion in domestic chicks, we focused on self-propulsion, using two video-animations representing a simple red circle moving at constant speed (speed-constant) or one that was changing its speed (accelerating and decelerating; speed-change). Using a six minutes spontaneous choice test for the two stimuli, we compared unlearned preferences for stimuli that autonomously change speed between VPA- and vehicle-injected chicks. We found that the preference for speed changes was abolished in VPA-injected chicks compared to vehicle-injected controls. These results add to previous findings indicating similar impairments for static social stimuli and suggest a specific effect of VPA on the development of mechanisms that enhance orienting towards animate stimuli. These findings strengthen the hypothesis of an early impairment of predispositions in the early development of ASD. Hence, early predispositions are a potentially useful tool to detect early ASD symptoms in human neonates and to investigate the molecular and neurobiological mechanisms underlying the onset of this neurodevelopmental disorder.